Development of Engine Oil Maintenance and Battery Health Monitoring through Short Messaging Service (SMS) - Muhammad Muizzuddin Nawi; Abd Fathul Hakim Zulkifli (Journal of Automotive Powertrain and Transportation Technology, 2025)
With proper care and proper maintenance, vehicle can be maintained to work as it supposed to and has longer life cycle. Vehicle maintenance for new vehicle monitored using service booklet while for some of older vehicle, the maintenance totally depends on owner awareness and most cases, they are using service note provided by service centre which are sticked on the windshield. Prior to this situation, the owner may not be notified because sometimes the vehicle may exceed the recommended mileage and date for next service. The aim of the project is to develop the vehicle maintenance monitoring through short messaging system (SMS) using Arduino Uno and GSM SIM900A module. The proposed project helps the vehicle user to monitor on the engine oil mileage and battery voltage on mobile phone. The vehicle owner can check and notified their vehicle next service using phone message. The project is developed using simple programming software and hardware. Arduino Uno as microcontroller to receive data from voltage sensor and send battery voltage through SMS. The push buttons used to represent the input from vehicle owner about the type of oil used during vehicle service to check the vehicle condition. The GSM module act as a message transmitter and receiver for user communication. The task was programmed into Arduino Uno using Arduino Integrated Development Environment (IDE). The development of this project helps the user to monitor vehicle condition especially for their maintenance schedule. The maximum percentage error was 3.2725% and lowest percentage error of 1.9787% of vot meter reading is measured. This project can be concluded that the device was successfully being developed and the functionality was observed.